Designed to Connect: David’s Programmed Emotional Responses in A.I. Artificial Intelligence (2001) - priyoto priyoto; Sri Marleni; Bayu Hari Yudanto; Amira Raihana Amalia (STIBA IEC JAKARTA, 2026)
This study examines the programmed emotional responses of David, the central humanoid robot in Steven Spielberg's A.I. Artificial Intelligence (2001), with a focus on emotional connections design between artificial beings and humans. The research employs a descriptive qualitative method, integrating film analysis and theories of human-AI interaction to explore the narrative and technological frameworks that shape David's emotional expressions. The findings indicate that while David's emotional programming successfully evokes empathy and connection, it also prompts critical discussions about the authenticity of artificial emotions and their implications for human relationships. This study contributes to the broader dialogue on the role of emotions in AI development and their potential societal impacts